Turismo de resistência : fortalecimento comunitário e exercício de liberdade : comunidade Mutuca/ território Mata Cavalo – MT - Fava, Bruna Mendes de (2022)
The objective of this thesis is to defend the counter-colonial tourism, alternative income, and cultural strengthening in resistance tourism of the quilombola community Mutuca - Território Mata Cavalo-MT. We intend to collectively examine with the Mutuca community, their local cultural practices and to prospect, community and researchers, the reedition of resistance tourism, built and carried out by the host community. As the research has a qualitative character, we carry out meetings with the community at different times, for observation in everyday and festive periods, and online meetings, five of them prior to the Covid 19 pandemic period and five after the beginning of the pandemic, and, in three of them, semi-structured interviews with the community were recorded. We also held participatory workshops to discuss the theme of tourism at community association meetings in the period before the pandemic, in addition to the extension project meetings. From the readings, workshops and meetings with the community, an experience initiative emerged that represents resistance tourism, the Baquité Sensorial project, which aimed to materialize the olfactory sensory experience of elements of the Mutuca's nature, bringing real and potential tourists closer to the quilombola community. Linked to the Baquité Sensorial project, analyzes of recorded narratives were carried out in onsite visits and online conversations and interviews with 8 community members, in addition to the coexistence during daily and festive activities of the quilombo. A documentary survey was also carried out on the process of titling and recognition of Mata Cavalo in official bodies and the use of the methodology of social cartography linked to the narratives of the oral history of the quilombolas of Mutuca. It was possible to perceive the community's desire to develop resistance tourism and, in the first workshops and actions of the Baquité Sensorial project, some of the contemporary cultural components were already identified as possible tourist attractions by the community, such as the scent and discharge waters, which they bring essences of the quilombo, typical dances, such as Cururu, Siriri, Afro and Congo dance, in addition to the use of gastronomy, such as fried banana, liqueurs and paçoca. Many of the quilombolas present in the workshops and interviews mentioned their festivals of saints and the Festa da Banana, the typical handicrafts, their healing practices, plants, herbs and the very characteristic of resistance and struggle as attractions that can be linked to tourism in the community. It is intended to defend resistance tourism as a counter-colonial action and economic alternative that strengthens the quilombola culture and consists of resistance to the hegemonic impositions that plague contemporary reality.